2006
DOI: 10.1128/aac.50.5.1768-1772.2006
|View full text |Cite
|
Sign up to set email alerts
|

Poly(I)-Poly(C 12 U) but Not Ribavirin Prevents Death in a Hamster Model of Nipah Virus Infection

Abstract: Clinical nonrandomized trials demonstrate some efficacy for ribavirin in the treatment of patients with severe Nipah virus-induced encephalitis. We report here that EICAR, the 5-ethynyl analogue of ribavirin, and the OMP-decarboxylase inhibitors 6-aza-uridine and pyrazofurin have strong antiviral activity against Nipah virus replication in vitro. Ribavirin and 6-aza-uridine were tested further in hamsters infected with a lethal dose of Nipah virus. The activity of these small-molecule inhibitors was compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 36 publications
2
99
0
Order By: Relevance
“…This may result in worsening of cardiac disease that has led to fatal and nonfatal myocardial infarctions (Shakil et al, 2002) while significant teratogenic and/ or embryocidal effects have also been indicated for ribavirin (Chutaputti, 2000). However, a recent study showed that the 5 ethyl analogue of ribavarin but not ribavarin was able to prevent mortality in five of six animals in a hamster model of NiV infection (Georges-Courbot et al, 2006) suggesting that other replication inhibitors may be effective against Henipaviruses. The lack of effective therapeutic modalities for Henipaviruses, their classification as biological safety level-4 (BSL4) pathogens, and their inclusion as National Institute of Allergy and Infectious Diseases (NIAID) Category C priority pathogens make novel antiviral drug development a high priority.…”
Section: Introductionmentioning
confidence: 96%
“…This may result in worsening of cardiac disease that has led to fatal and nonfatal myocardial infarctions (Shakil et al, 2002) while significant teratogenic and/ or embryocidal effects have also been indicated for ribavirin (Chutaputti, 2000). However, a recent study showed that the 5 ethyl analogue of ribavarin but not ribavarin was able to prevent mortality in five of six animals in a hamster model of NiV infection (Georges-Courbot et al, 2006) suggesting that other replication inhibitors may be effective against Henipaviruses. The lack of effective therapeutic modalities for Henipaviruses, their classification as biological safety level-4 (BSL4) pathogens, and their inclusion as National Institute of Allergy and Infectious Diseases (NIAID) Category C priority pathogens make novel antiviral drug development a high priority.…”
Section: Introductionmentioning
confidence: 96%
“…It is a water-soluble synthetic nucleoside with broad-spectrum antiviral properties that has been shown to be active in vitro against many viruses (Huffman et al, 1973;Gururangan et al, 1990;Honda et al, 1994;Ishii et al, 1996;Chong et al, 2001;Graci & Cameron, 2006;Elia et al, 2008). Although RBV was used as an antiviral agent during the first NiV outbreak in 1999 in Malaysia, its antiviral properties could not be confirmed in the generally accepted hamster model (Georges-Courbot et al, 2006). In the case of SSPE the treatment with inosiplex (isoprinosine), intraventricular alpha interferon and RBV, which is applied in many cases, may at best prolong the disease course (Weissbrich et al, 2003).…”
mentioning
confidence: 99%
“…No vaccines or specific antiviral drugs are currently available for NiV. Although patients from the Malaysian outbreak who received ribavirin showed a lower mortality rate (Chong et al, 2001), ribavirin was unable to protect NiV-infected hamsters from fatal disease (Georges-Courbot et al, 2006).The genomes of NiV and HeV are 18 246 and 18 234 nt, respectively, making them significantly larger than most other paramyxoviruses, with the exceptions of rodentborne Beilong and J viruses (Jack et al, 2005;Li et al, 2006). The N, P and L proteins are required and sufficient for mini-genome replication, similar to other members of the subfamily Paramyxovirinae (Halpin et al, 2004).…”
mentioning
confidence: 99%
“…No vaccines or specific antiviral drugs are currently available for NiV. Although patients from the Malaysian outbreak who received ribavirin showed a lower mortality rate (Chong et al, 2001), ribavirin was unable to protect NiV-infected hamsters from fatal disease (Georges-Courbot et al, 2006).…”
mentioning
confidence: 99%